Structural equation analysis of the role of appearance-related self-conscious emotions on flow in athletes: The mediating role of autonomous motivation - Urfa, O.; Asçi, F. H.; Karadag, D. (Journal of Sports Sciences, 2025)
The current study aimed to investigate the mediating role of autonomous motivation in the relationship between appearance-related self-conscious emotions (shame, guilt, authentic pride, and hubristic pride) and flow in athletes. The sample consisted of 217 athletes (57.6% male) aged between 18 and 39 years old (Mage = 21.77, SD = 4.53). The cross-sectional data were analyzed using structural equation modelling with bootstrapping method. Regarding direct effects, autonomous motivation was negatively correlated with shame and hubristic pride and positively correlated with authentic pride. Flow was positively related to autonomous motivation and hubristic pride. Regarding indirect effects, flow was negatively predicted by shame and hubristic pride and positively predicted by authentic pride through autonomous motivation. These results highlight the importance of autonomous motivation in the relationship between self-conscious emotions and flow in athletes. In particular, shame and authentic pride predicted flow fully through autonomous motivation. In conclusion, autonomous motivation mediates the relationship between self-conscious emotions and flow in athletes. We therefore speculate that improving autonomous motivation in sport psychology studies may help improve flow in athletes.